The Effect of Motivation and Audio Visual Media-Based CTL Method on News Text Writing Skills - Susilawati, Wiwit; Afnita, Afnita (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study is entitled